The Boyfriend - McFadden, Freida (Naperville, Illinois : Poisoned Pen Press, 2024)
"Sydney Shaw, like every single woman in New York, has terrible luck with dating. Then she meets Tom. Tom is utterly perfect. He's charming, handsome, and works as a doctor at a local hospital. Before she knows it, Sydney is swept off her feet. But the brutal murder of a young woman--the latest in a string of deaths across the coast--confounds police. The primary suspect? A mystery man who dates his victims before he kills them. Sydney should feel safe. After all, she has Tom, the man of her dreams. But she can't shake her own horrifying suspicions that the perfect man may not be as perfect as he seems. Because someone is watching her every move, and if she doesn't get to the truth soon, she'll be the killer's next victim."--.
new book 2024 fall.
Keywords: Man-woman relationships; Dating; Psychological Fiction; Serial murderers; Suspense fiction; Novels; Thriller fiction; Romance fiction